STUDI KESESUAIAN PERAIRAN UNTUK EKOWISATA DIVING DAN SNORKELING DI PERAIRAN PULAU KERAMAT, KEBUPATEN SUMBAWA PROVINSI NUSA TENGGARA BARAT - Widhianingrum, Indriani; Indarjo, Agus; Pratikto, Ibnu (977-2407769)
Keramat Island is an uninhabited island and one of the favored tourism area in Sumbawa which has considerable potential as a tourist area with beautiful and unspoiled natural scenery, away from the activities surrounding communities, with a white sandy expanse full of flora and fauna and the pollution level is very small.The research was conducted in the waters of Keramat Island, Sumbawa district on September - November 2011 with the aim to determine the potential that exists in the waters of Keramat Island and assess the suitability of Keramat Island waters as diving and snorkeling ecotourism.The method used in this research is descriptive exploratory method. The analysis used in this study is an analysis of the water suitability, that is by comparing the characteristics and quality of the waters with the land usage requirements for certain tourist activities.Results of the study showed that the Keramat Island waters has a good potential for Diving and Snorkeling with the potential for the highest live coral reefs 84.15% and the lowest 38%, 5-11 Life form coral and various fish species are 40-127 species. The greater the percentage of coral reefs in the waters, the greater the species of fish and coral life form. Diving suitability of Keramat Island waters is in the S1 category (very appropriate) with IKW at Station 1-6 ranged between 90-100% and the snorkeling suitability of Keramat Island waters is in the S1 category (very appropriate) with IKW at Station 7-12 of 100%.